Let A be the event of a positive test result and B the event that a given person has the disorder. We're told
[tex]P(A \mid B) = 0.96[/tex]
[tex]P(A \mid B^c)=0.03[/tex]
[tex]P(B)=0.14[/tex]
and we want to find [tex]P(B\mid A)[/tex]. This follows directly from Bayes' theorem:
[tex]P(B\mid A)=\dfrac{P(A\cap B)}{P(A)}=\dfrac{P(A\cap B)}{P(A\cap B)+P(A\cap B^c)}[/tex]
[tex]P(B\mid A)=\dfrac{P(A\mid B)P(B)}{P(A\mid B)P(B)+P(A\mid B^c)P(B^c)}[/tex]
[tex]P(B\mid A)=\dfrac{0.96\cdot0.14}{0.96\cdot0.14+0.03\cdot0.86}\approx\boxed{0.84}[/tex]